The national policy on languages, December 1987-March 1990 : report to the Minister for Employment, Education and Training - Australian Advisory Council on Languages and Multicultural Education (Canberra : The Advisory Council, 1990)
Progress report on programs under National Policy on Languages including proposals and activities of National Aboriginal Languages Program including list of projects funded.
Cover title.
Keywords: Language policy -- Australia; Language and education -- Australia; Multilingualism -- Australia; Language - Maintenance; Language - Bilingualism and multilingualism; Community organisations - Cultural; Settlement and contacts - Ethnic groups, immigration and multiculturalism; Education - Language - Indigenous languages; Australia